Implementasi Fungsi Badan Permusyawaratan Desa (BPD) Dalam Mewujudkan Sustainable Development Goals (SDGs) Desa - I Wayan Sutrisna (Universitas Mahendradatta Denpasar, 2021)
The paradigm of village development is changing rapidly, so it needs the village government apparatus that can really adjust to the changing situation. The current government is paying very serious attention in efforts to reduce poverty in the village. This is done because with sustainable village development will provide benefits to improve the economy of the community, thereby impacting on improving the welfare of the community. Community participation in the development process is the main key to successful development implementation because it places the community as the driving force or as the subject of development not just as an object. Development with a participatory approach makes the community feel responsible for every process and results of development. The priority of village development has now been directed towards sustainable development goals (SDGs). BPD as a